Risk Factors for Academic Backwardness: An Intervention Study - Patil, Manjula; Hundekar, P S; Patil, S S (Indian Journal of Extension Education, 2020)
Academic backwardness in school is not simply an intellectual matter, but that it is a condition where normalÂ school achievement has been prevented by a variety of interacting influences. Therefore, the present study examined the risk factors which are associated with academic backwardness among school children. The sampleÂ consisted of 76 academically backward children of both the gender studying in 8th and 9th standards from two villages of Dharwad taluk. A structured checklist developed by AICRP â€“ CD scientists on reasons for academic backwardness was used to assess the causal factors for academic underachievement. Results revealed that majority of children expressed hard to study some subjects, slow in writing and inability to give answers to allÂ the questions in the exams quoted as academic reasons. In familial factors children perceived that their homeÂ environment is not conducive for the study, family income and parentâ€™s occupation disturbing their studies, parents and family members did not contributing much to their studies and lack of expected cooperation fromÂ family members. With respect to health problems worry, tension and stress during study, Tiredness due to the long distance of school from home, lack of concentration, headache and restlessness making the child to underachieve in the school. The intervention was found to be effective in modifying the environment of school,Â home and also the behavior of students, parents and teachers. Hence reducing the risk factors related to academic, familial and health aspects.